Reduction of high-frequency network oscillations (ripples) and pathological network discharges in hippocampal slices from connexin 36-deficient mice - Maier, Nikolaus (Blackwell Science Inc, 2002)
Recent evidence suggests that electrotonic coupling is an important mechanism for neuronal synchronisation in the mammalian cortex and hippocampus. Various types of network oscillations have been shown to depend on, or be sharpened by, gap junctions between inhibitory interneurones or excitatory projection cells. Here we made use of a targeted disruption of the gene coding for Cx36, a recently discovered neuronal gap junction subunit, to analyse its role in hippocampal network behaviour. Mice lacking Cx36 are viable and lack obvious morphological or behavioural abnormalities. Stimulation of afferent and efferent fibre pathways in hippocampal slices revealed a largely normal function of the synaptic circuitry, including tetanically evoked network oscillations. Spontaneous sharp waves and ripple (∼200 Hz) oscillations, however, occurred less frequently in slices from Cx36 -/- mice, and ripples were slightly slower than in littermate controls. Moreover, epileptiform discharges elicited by 4-aminopyridine were attenuated in slices from Cx36 -/- mice. Our findings indicate that Cx36 plays a role in the generation of certain forms of network synchronisation in the hippocampus, namely sharp wave-ripple complexes and hypersynchronous epileptiform discharges.